Puzzling out the past : studies in Northwest Semitic languages and literatures in honor of Bruce Zuckerman - Zuckerman, Bruce.; Lundberg, Marilyn J.; Fine, Steven.; Pitard, Wayne T. (Culture and History of the Ancient Near East, 2012)
Bruce Zuckerman has transformed the way we look at ancient Semitic inscriptions. Through his efforts, the most important inscriptions of biblical times have been reread and the history of the biblical and Second Temple periods reimagined. He has made contributions to the fields of biblical studies and modern Judaism, and, in founding Maarav: A Journal for the Study of the Northwest Semitic Languages and Literatures , has made the research of many scholars available to the scholarly community. The series of articles included here honor his many contributions through discussions of a wide variety of inscriptional materials, Biblical texts, archaeology, lexicography and teaching methodology. Included in the volume is a republication of his path breaking exhibition catalogue, Puzzling Out the Past .